영양소 결핍으로 유도한 성장장애 흰쥐에서 龍玉膏가 성장 및 학습효과에 미치는 영향 - 공인표(In Pyeo Kong); 차윤엽(Yun Yeop Cha) (동의생리병리학회지, 2008)
Effects of Kyungohkgo Ga Nokyong(Yongohkgo) on growth development and learning ability were investigated growth and intellectual impairment rat with insufficient nutrition diet. We divided male Sprague-Dawley rats into 4 groups. They were Normal group, Growth deficiency rat with insufficient nutrition diet group, Growth deficiency rat with 0.1% Yongohkgo group and 0.2% Yongohkgo group. They were administered for 5 weeks. We measured body weight, and morris water maze test in escape distance, escape time and escape speed, serum growth hormone, insulin-like growth factor and thyroid stimulating hormone, RBC, concentration of Hb and PCV ratio, total WBC and its composition, the values of GOT and GPT activities. The results are as follows that Yongohkgo 0.1%, 0.2% groups were showed significantly different than control groups in body weight and the counts of RBC. In the morris water maze test, in escape distance and escape time, in concentration of Hb and PCV ratio, 0.2% Yongohkgo group were significantly different than control groups. Serum growth hormone, insulin- like growth factor and thyroid stimulating hormone showed a tendency to increase in Yongohkgo groups. The counts of total WBC and its composition, GOT, GPT activities showed no significantly different in all treatment groups. These results suggested that Yongohkgo have an effect of promoting growth and learning ability of rats and might be effect to treat various kinds f growth and learning ability delay in children. KCI Citation Count: 1